2019
DOI: 10.1093/mnras/stz1032
|View full text |Cite
|
Sign up to set email alerts
|

ALMA reveals a pseudo-disc in a proto-brown dwarf

Abstract: We present the observational evidence of a pseudo-disc around the proto-brown dwarf Mayrit 1701117, the driving source of the large-scale HH 1165 jet. Our analysis is based on ALMA 12 CO (2-1) line and 1.37 mm continuum observations at an angular resolution of ∼0.4 . The pseudo-disc is a bright feature in the CO position-velocity diagram (PVD), elongated in a direction perpendicular to the jet axis, with a total (gas+dust) mass of ∼0.02 M , size of 165-192 AU, and a velocity spread of ±2 km s −1 . The large ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…Therefore, the velocity difference is marginal, and we cannot ascertain clearly whether there is a velocity gradient or not. The radius of 4000 AU is between a large value of ∼ 15, 00030, 000 AU of the archetypal pseudo-disk associated with the Class 0 protostar L1157 (Looney et al 2007) and a small value of 165192 AU around a proto-brown dwarf (Riaz et al 2019). Ohashi et al (1997) investigated the specific angular momentum of the rotating protoplanetary disk and the (collapsing) envelope (or pseudo-disk) as well as the molecular cloud core.…”
Section: G210mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the velocity difference is marginal, and we cannot ascertain clearly whether there is a velocity gradient or not. The radius of 4000 AU is between a large value of ∼ 15, 00030, 000 AU of the archetypal pseudo-disk associated with the Class 0 protostar L1157 (Looney et al 2007) and a small value of 165192 AU around a proto-brown dwarf (Riaz et al 2019). Ohashi et al (1997) investigated the specific angular momentum of the rotating protoplanetary disk and the (collapsing) envelope (or pseudo-disk) as well as the molecular cloud core.…”
Section: G210mentioning
confidence: 99%
“…N 2 D + is one of the most important molecules, as it allows us to investigate the densest regions of molecular cloud cores (Kong et al 2017;Salinas et al 2017;Aikawa et al 2018;Riaz et al 2019;van 't Hoff et al 2018;Punanova et al 2018;Murillo et al 2018;Tobin et al 2019;Tokuda et al 2019). N 2 H + is known to be a molecule weakly affected by depletion in cold, dense regions (Bergin et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the only confirmed pre-BD is Oph B-11 (André et al 2012) and there are pre-BD candidates both in Taurus (Palau et al 2012;Tokuda et al 2019) and Barnard 30 (Huélamo et al 2017;Barrado et al 2018). Regarding proto-BDs, one excellent Class 0/I candidate has been identified in Perseus (Palau et al 2014) and other candidates are proposed in Taurus (Apai et al 2005;Barrado et al 2009;Palau et al 2012;Morata et al 2015;Dang-Duc et al 2016), Chamaeleon II (de Gregorio-Monsalvo et al 2016), Ophiuchus (Whelan et al 2018;Riaz et al 2018;Kawabe et al 2018), Serpens (Riaz et al 2016(Riaz et al , 2018, and σ Orionis (Riaz et al 2015(Riaz et al , 2017(Riaz et al , 2019, although many of these may also be more evolved Class I objects. Finally, the search and study of very low luminosity objects (VeLLOs) have revealed sources that show proto-BD characteristics (Bourke et al 2006;Lee et al 2009Lee et al , 2013Lee et al , 2018Kauffmann et al 2011;Kim et al 2019; also see the references in Table 4 of Palau et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulation studies have provided an understanding of the various phenomenon of the brown dwarf formation processes, whether it is a star-like formation via gravitational core collapse (e.g., Machida et al 2009), or alternative mechanisms of formation via disc fragmentation and as ejected embryos (Stamatellos & Whitworth 2008;Goodwin & Whitworth 2007;Bate 2012). The physical scales of early-stage Class 0/I proto-brown dwarfs (proto-BDs) are expected to be at least ten times smaller than a low-mass protostar (e.g., Riaz et al 2019a;Machida et al 2009), which makes it difficult to resolve the inner few tens of au scales where various processes are expected to originate from. In our recent work on ALMA CO line and continuum observations of a Class I proto-BD in Orion, we showed on the basis of physical+chemical modelling that the observed CO line emission is tracing the infall+rotational kinematics originating from a pseudo-disc structure with a total (gas+dust) mass of ∼0.02 M and a size of 178±16 au in this proto-BD system (Riaz et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…The physical scales of early-stage Class 0/I proto-brown dwarfs (proto-BDs) are expected to be at least ten times smaller than a low-mass protostar (e.g., Riaz et al 2019a;Machida et al 2009), which makes it difficult to resolve the inner few tens of au scales where various processes are expected to originate from. In our recent work on ALMA CO line and continuum observations of a Class I proto-BD in Orion, we showed on the basis of physical+chemical modelling that the observed CO line emission is tracing the infall+rotational kinematics originating from a pseudo-disc structure with a total (gas+dust) mass of ∼0.02 M and a size of 178±16 au in this proto-BD system (Riaz et al 2019a). By modelling the observed position and velocity offsets in the CO line position-velocity diagram, we were able to constrain the kinematical age of this system to be 0.03±0.01 Myr (Riaz et al 2019a).…”
Section: Introductionmentioning
confidence: 99%